New Trends in Electric Machines Technology and Applications - Delgado-Prieto, Miguel; Antonino Daviu, José A.; Osornio Rios, Roque A. (IntechOpen, 2023)
Electric machines are widely used in industry, energy, and transport, among other sectors. They are also heavily researched with scientific and technological efforts focusing on three main areas: electric motor technologies, supervision and maintenance strategies, and control schemes. This book provides a comprehensive overview of the technology and applications of electric machines. It is organized into two sections on maintenance and control. Chapters address such topics as signal processing and artificial intelligence, fault detection and identification schemes, predictive maintenance strategies, direct torque control and Lyapunov-based sensorless control, and more.